Model of Teaching Speaking Practiced in Toraja Christian University of Indonesia - Roni La’biran (Peneliti.net, 2020)
The objectives of this research are to describe model teaching speaking on that applied by the lecturer at Toraja Christian university of Indonesia in teaching speaking, and to describe students’ perception toward the model in teaching speaking. The researcher employed a qualitative method for the study. The data resource for the research is lecturer from Toraja Christian University of Indonesia. Data were collected through observation, and interviews. Results show phase in teaching speaking model : create goal, course interesting and contextual topics, students’ monitoring, good management in classroom, create medias, and teaching reflection, teaching interacting model, and evaluation, interviews indicate that the student have positive perception toward the model in teaching speaking used by this lecturer in teaching speaking class.